2007
DOI: 10.1080/15563650701397035
|View full text |Cite
|
Sign up to set email alerts
|

Decline in pesticide poisonings in the United States from 1995 to 2004

Abstract: Pesticide poisonings and injuries appear to have declined in the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 4 publications
1
10
0
1
Order By: Relevance
“…In California, use trends for all cholinesterase-inhibiting pesticides (including carbamates and organophosphates) have steadily decreased from about 17 million lb in 1995 to about 7 million lb in 2006 (12). A review of pesticide poisonings in the United States based on incidents reported to Poison Control Centers (PCCs) during the 1995-2004 period indicated that poisonings from organophosphate pesticides had declined by 72%, mostly due to chlopyrifos and diazinon being phased out from residential uses (13).…”
Section: Production and Usementioning
confidence: 99%
“…In California, use trends for all cholinesterase-inhibiting pesticides (including carbamates and organophosphates) have steadily decreased from about 17 million lb in 1995 to about 7 million lb in 2006 (12). A review of pesticide poisonings in the United States based on incidents reported to Poison Control Centers (PCCs) during the 1995-2004 period indicated that poisonings from organophosphate pesticides had declined by 72%, mostly due to chlopyrifos and diazinon being phased out from residential uses (13).…”
Section: Production and Usementioning
confidence: 99%
“…U.S. EPA uses poison control center (PCC) data as a source of information on pesticide exposure because this is a nationwide database, and it has a standardized format and definitions that permit comparisons over a period of years (APCC, 2002;Blondell, 2007).…”
Section: Toxic Exposure Surveillance System (Tess) (American Associatmentioning
confidence: 99%
“…The significant decline in OP incidents reported to PCCs in the United States during 1995 -2004 was observed despite the overall proportion of pesticide exposures reported to PCCs remaining relatively consistent during this period, and in fact the population that was covered by PCCs in the United States increased over the same time period. Blondell (2007) reported a decline in the number of incidents of unintentional pesticide illnesses and injuries by type for the United States using PCC data for 1995-2004. At least 83% of the U.S. population was included in PCC catchment areas reporting to the national database for 1995 -2003 based on U.S. census data.…”
Section: Toxic Exposure Surveillance System (Tess) (American Associatmentioning
confidence: 99%
See 2 more Smart Citations